A method for preparing biocompatible diamond composite material at low temperature

By depositing a diamond film layer at a low temperature on the surface of a bioactive deposition material, the problem of lack of biological activity in the existing diamond composite materials is solved, and the high mechanical properties and corrosion resistance of biocompatible diamond composite materials are achieved.

CN119753678APending Publication Date: 2025-04-04SINOMA SYNTHETIC CRYSTALS (SHANDONG) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839386.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing diamond composite materials lack bioactivity and are difficult to meet the requirements of high mechanical properties, biocompatibility and corrosion resistance at the same time.

Method used

By using a low-temperature preparation method, biocompatible diamond composite materials are prepared by depositing a diamond film layer on the surface of a bioactive deposition material, excitating plasma using a microwave field, controlling the deposition temperature between 350-750°C, and polishing and disinfection.

Benefits of technology

The bioactivity, mechanical properties and corrosion resistance of diamond composite materials have been greatly improved, and they have high binding strength, wear resistance and biocompatibility.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for preparing biocompatible diamond composite materials at low temperature, comprising the following steps: selecting a bioactive deposition material and pretreating the deposition material; placing the pretreated deposition material on the upper part of a substrate inside a deposition chamber, with the deposition surface of the deposition material facing upwards; a rotating stage is provided inside the deposition chamber, and the substrate is placed on the rotating stage; turning on a microwave generator in the deposition chamber; introducing a carbon source and a hydrogen source into the deposition chamber, and controlling the deposition temperature in the deposition chamber at 350-750℃ through the microwave generator; turning on the rotating stage; depositing a diamond film layer on the upper surface of the deposition material to obtain a crude biocompatible diamond composite material; polishing and grinding the surface of the crude biocompatible diamond composite material to obtain a biocompatible diamond composite material; thus achieving the preparation of a diamond composite material with bioactivity, high mechanical properties, high bonding strength, resistance to damage, and high corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of diamond composite material preparation, and in particular to the field of a method for preparing a diamond composite material with biocompatibility at low temperature. Background Art

[0002] With the continuous advancement of medical technology, the standards for human skeleton materials are getting higher and higher, and the development of ideal medical materials is particularly necessary. Ideal orthopedic implant materials not only need to have good biocompatibility and bioactivity, but also need to have sufficient hardness, appropriate strength, excellent physical and chemical properties, sufficient load capacity, good wear resistance and corrosion resistance. Therefore, ideal materials have the following requirements: (1) In terms of mechanical properties, the implanted material should have sufficient strength and toughness, appropriate hardness and elasticity, good fatigue resistance, creep resistance and necessary wear resistance and self-lubrication. (2) In terms of corrosion resistance, the corrosion of common materials mainly includes general uniform corrosion, intergranular corrosion, galvanic corrosion, wear corrosion and fatigue corrosion. This requires that the surface of the implanted material does not undergo chemical reactions to cause corrosion when exposed to the physiological environment of the human body, that there is no wear between the gap between the implanted material and the human tissue, and that the implanted material does not suffer damage or fracture after long-term repeated movement, so as to meet the requirements of the indicators. (3) In terms of biocompatibility, the implanted material is required not to cause damage, poisoning or other adverse effects on human tissues, not to have rejection reactions with tissues and organs in the human body, and to be closely integrated with the surrounding bones and tissues and have biological activity. Among the above three points, biocompatibility is generally considered to be the key indicator to measure the quality of biomaterials.

[0003] Traditional diamond composites have high mechanical properties and high corrosion resistance, but do not have good biological activity.

[0004] Therefore, how to prepare diamond composite materials with biological activity, high mechanical properties, high bonding strength, not easy to be damaged, and high corrosion resistance has become a difficult problem that needs to be solved urgently in this field. Summary of the invention

[0005] In order to solve the above technical problems, a method for preparing a biocompatible diamond composite material at low temperature is provided to achieve the preparation of a diamond composite material with biological activity, high mechanical properties, high bonding strength, not easy to be damaged, and high corrosion resistance.

[0006] According to the present invention, a method for preparing a biocompatible diamond composite material at low temperature is provided, comprising the following steps:

[0007] Selecting a deposition material with biological activity and pre-treating the deposition material;

[0008] Placing the pre-treated deposition material on the upper part of the substrate in the deposition chamber, with the deposition surface of the deposition material facing upward; a rotating table is provided in the deposition chamber, and the substrate is arranged on the rotating table;

[0009] Turning on the microwave generator in the deposition chamber;

[0010] A carbon source and a hydrogen source are introduced into the deposition chamber, and the deposition temperature in the deposition chamber is controlled at 350-750° C. by a microwave generator; a rotating table is turned on; a diamond film layer is deposited on the upper surface of the deposition material to obtain a crude biocompatible diamond composite material;

[0011] The rough surface of the biocompatible diamond composite material is polished and ground to obtain the biocompatible diamond composite material;

[0012] Preferably, when the rough surface of the biocompatible diamond composite material is polished and ground, 10-15 μm to 22-36 μm diamond micropowder is used for grinding, and 0-0.5 μm to 6-10 μm diamond micropowder is used for polishing;

[0013] After the rough surface of the biocompatible diamond composite material is polished and ground, it is disinfected. First, use medical alcohol for preliminary cleaning, then use a neutral multi-enzyme cleaner, and then use an ultrasonic cleaner to clean it. Boil it for disinfection. Do not use lubricants to lubricate it to avoid residues. After drying in a drying cabinet, package it, and then use a high-temperature and high-pressure sterilizer or an epoxy-acetylene sterilizer for sterilization to meet the conditions for use.

[0014] Compared with the prior art, the present invention has the following beneficial effects: the deposition material having biological activity is conducive to achieving the diamond composite material in which diamond is deposited on the surface of the deposition material having biological activity;

[0015] Pre-treating the deposited material is beneficial to achieving high bonding strength between the diamond film and the deposited material;

[0016] Placing the pre-treated deposition material on the upper part of the substrate in the deposition chamber, wherein the substrate is arranged on a rotating table, is conducive to achieving uniform deposition of the diamond film on the surface of the deposition material;

[0017] The deposition temperature in the deposition chamber is controlled at 350-750°C by a microwave generator, so that the reaction gas is excited into a plasma state under the action of the microwave field. The plasma is formed in a spherical shape on the diamond substrate. The high temperature of the plasma is used to heat the substrate to a certain temperature, and the carbon-containing gas is mixed with supersaturated hydrogen at high temperature to deposit a diamond film on the surface of the material. Since the temperature of the deposition chamber is not high, it is beneficial to reduce the defects and internal stress of the diamond film, and to reduce the lattice distortion and defect formation caused by high temperature, thereby improving the mechanical properties of the diamond composite material.

[0018] Furthermore, the deposition material includes one of zirconium oxide and silicon nitride.

[0019] The beneficial effect of adopting the previous step is that by depositing a material including one of zirconium oxide and silicon nitride, the biological activity of the diamond composite material is improved.

[0020] Further, the pretreatment of the deposition material comprises the following steps: surface treatment of the deposition material, preparation of a surface treatment solution, wherein the surface treatment solution comprises H2SO4 and H2O2 in a volume ratio of 1:10, or the surface treatment solution comprises an alkali solution with a mass fraction of 1%-2%;

[0021] Soaking the deposited material in the surface treatment solution for ≥2 minutes;

[0022] The deposited material is then ultrasonically shaken in water for 10-20 minutes, and then cleaned with ethanol and wiped dry for later use.

[0023] The beneficial effect of adopting the previous step is that an uneven corrosion surface is formed on the surface of the deposited material through the surface treatment liquid, which is conducive to high bonding strength between the diamond film layer and the deposited material; and by ultrasonically oscillating in water for 10-20 minutes, then cleaning with ethanol and drying, the problem of reduced bonding strength between the diamond film layer and the deposited material caused by residual surface treatment liquid on the surface of the deposited material is avoided.

[0024] Furthermore, the matrix material is one of silicon, molybdenum and graphite.

[0025] The beneficial effect of adopting the previous step is that the thermal conductivity of the substrate material is conducive to avoiding the problem of deformation of the deposited material during the substrate supporting the deposited material during the heating deposition process, thereby causing the problem of low bonding strength between the diamond film and the deposited material.

[0026] Furthermore, the hydrogen source introduced into the deposition chamber is hydrogen; the carbon source introduced is methane;

[0027] The hydrogen source flow rate is 450-520 ml / min, and the carbon source flow rate is 20-30 ml / min.

[0028] The beneficial effect of adopting the previous step is that by the hydrogen source flow rate of 450-520ml / min and the carbon source flow rate of 20-30ml / min, a diamond film can be deposited on the surface of the base material at a low temperature, and the deposited diamond film has a high bonding strength with the base material, a low amount of graphite impurities in the diamond film, and a certain porosity, which is conducive to achieving high mechanical properties (high strength and high toughness) of the diamond composite material and improving biological activity.

[0029] Furthermore, a carbon source and a hydrogen source are introduced into the deposition chamber, and oxygen is introduced into the deposition chamber at a flow rate of 2-3 ml / min.

[0030] The beneficial effect of adopting the previous step is that the oxygen flow rate of 2-3 ml / min is conducive to increasing the gas activity in the reaction chamber even at a not very high temperature, separating the carbon element, thereby facilitating the deposition of diamond on the surface of the substrate material.

[0031] Furthermore, octamethylcyclotetrasiloxane is introduced into the deposition chamber at the same time as the carbon source, hydrogen source and oxygen source, and the flow rate of the octamethylcyclotetrasiloxane is 1-2 ml / min.

[0032] The beneficial effect of the above step is that by also introducing octamethylcyclotetrasiloxane at a flow rate of 1-2 ml / min, silicon is doped in the transition layer deposited on the surface of the deposited material, thereby facilitating the improvement of the bonding strength between the deposited material and the diamond film layer without reducing the strength of the diamond composite material.

[0033] Furthermore, when the carbon source and the hydrogen source are introduced into the deposition chamber, the gas inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle, and the rotation angle is 10-30°;

[0034] The rotation speed of the rotating table is 0.2-0.3r / min;

[0035] The deposition rate on the deposition material surface is 4-5μm / h.

[0036] The beneficial effect of the above step is that when the carbon source and the hydrogen source are introduced, the air inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle, and the rotation angle is 10-30°, which is conducive to achieving uniform diamond film deposition on the surface of the deposition material and avoiding cracking or low bonding strength of the diamond film deposited on the edge of the deposition material;

[0037] The rotation speed of the rotating table is 0.2-0.3 r / min, which is conducive to achieving uniform diamond film deposition on the surface of the deposition material;

[0038] By setting the deposition rate on the surface of the deposited material at 4-5 μm / h, the graphite phase deposited during the low-temperature deposition process is washed away. At the same time, a certain porosity exists in the diamond film layer, which is beneficial to improving the biological activity. This rate avoids too low production efficiency.

[0039] Furthermore, the flow rates of the carbon source and hydrogen source are adjusted in sections;

[0040] The flow rate of the first section carbon source is 20-22 ml / min, the flow rate of the hydrogen source is 490-520 ml / min, and the flow rate of octamethylcyclotetrasiloxane is 1-2 ml / min;

[0041] The second section has a carbon source flow rate of 23-26 ml / min, a hydrogen source flow rate of 490-520 ml / min, and an oxygen flow rate of 2-3 ml / min;

[0042] The carbon source flow rate in the third section is 27-30 ml / min, and the hydrogen source flow rate is 460-480 ml / min;

[0043] The carbon source flow rate in the fourth section is 0, and the hydrogen source flow rate is 460-480 ml / min.

[0044] The beneficial effect of the above step is that the carbon source flow rate of the first section is 20-22 ml / min, the hydrogen source flow rate is 490-520 ml / min; the octamethylcyclotetrasiloxane flow rate is 1-2 ml / min; a transition layer is formed on the surface of the deposited material, and the transition layer includes diamond and silicon elements, which is beneficial to improving the bonding strength between the deposited material and the diamond film layer without reducing the strength of the diamond film layer; at the same time, the carbon source flow rate is low, so that the deposited diamond contains certain pores in the transition layer, which is beneficial to improving the biological strength of the diamond composite material;

[0045] The flow rate of the carbon source in the second stage is 23-26 ml / min, the flow rate of the hydrogen source is 490-520 ml / min, and the flow rate of the oxygen is 2-3 ml / min; the flow rate of the carbon source is low, so that the deposited diamond layer contains certain pores, and the flow rate of the hydrogen source is high, which is conducive to eliminating the graphite phase appearing in the low-temperature deposition process and is conducive to the generation of pores;

[0046] The carbon source flow rate through the third stage is 27-30 ml / min, and the hydrogen source flow rate is 460-480 ml / min; this is conducive to the higher density of diamond deposited in this layer, thereby improving the strength and wear resistance of the diamond composite material;

[0047] In the fourth stage, the carbon source flow rate is 0 and the hydrogen source flow rate is 460-480 ml / min, which is beneficial to eliminate the graphite phase in the deposited diamond.

[0048] Furthermore, the deposition temperature in the first deposition chamber is controlled at 600-750°C; the deposition temperature in the second deposition chamber is controlled at 350-450°C; the deposition temperature in the third deposition chamber is controlled at 460-560°C; and the deposition temperature in the fourth deposition chamber is controlled at 570-750°C.

[0049] The beneficial effect of the above step is that the deposition temperature in the first deposition chamber is controlled at 600-750°C, which is conducive to uniformly doping silicon elements into the diamonds of the transition layer and avoiding the formation of graphite phase.

[0050] By controlling the deposition temperature in the second deposition chamber to 350-450°C, it is helpful to avoid the problem of reduced porosity due to the growth of diamond grains; it is also helpful to avoid the problem of increased internal defects and internal stress of the diamond film due to excessively high temperature, that is, it is helpful to reduce lattice distortion and defect formation caused by high temperature;

[0051] By controlling the deposition temperature in the third deposition chamber to 460-560° C., it is beneficial to avoid the generation of graphite phase in the surface layer of the generated diamond film, and the surface strength of the diamond phase on the surface of the diamond film layer is high, and it is also beneficial to avoid the problem of internal defects of the diamond film caused by excessively high temperature;

[0052] By controlling the deposition temperature in the fourth deposition chamber to 570-750°C, it is beneficial to the growth of grains on the surface of the diamond film layer, thereby increasing the strength and wear resistance. At the same time, heating up and then cooling down without the introduction of a carbon source is beneficial to eliminating the stress in the diamond film generated in the early stage, and is beneficial to eliminating the graphite phase that appears under the action of a hydrogen source, thereby further improving the mechanical properties of the diamond composite material. DETAILED DESCRIPTION

[0053] In order to better understand the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments.

[0054] Embodiment 1:

[0055] This embodiment provides a method for preparing a biocompatible diamond composite material at low temperature, comprising the following steps:

[0056] Selecting a deposition material with biological activity, and pre-treating the deposition material; the deposition material includes zirconium oxide; the pre-treating of the deposition material includes the following steps: surface treating the deposition material, preparing a surface treatment liquid, the surface treatment liquid includes H2SO4 and H2O2 in a volume ratio of 1:10;

[0057] Soaking the deposited material in the surface treatment solution for 2.5 minutes;

[0058] The deposited material was then ultrasonically shaken in water for 15 min, washed with ethanol, and dried for later use.

[0059] The pretreated deposition material is placed on the upper part of the substrate inside the deposition chamber, with the deposition surface of the deposition material facing upward; a rotating table is provided inside the deposition chamber, and the substrate is arranged on the rotating table; the substrate is made of molybdenum.

[0060] Turning on the microwave generator in the deposition chamber;

[0061] A carbon source and a hydrogen source are introduced into the deposition chamber, and the deposition temperature in the deposition chamber is controlled at 550° C. by a microwave generator; a rotating table is turned on; a diamond film layer is deposited on the upper surface of the deposition material to obtain a crude biocompatible diamond composite material;

[0062] The hydrogen source introduced into the deposition chamber is hydrogen; the carbon source introduced is methane;

[0063] The hydrogen source flow rate is 485 ml / min, and the carbon source flow rate is 25 ml / min;

[0064] A carbon source and a hydrogen source are introduced into the deposition chamber, and at the same time, oxygen is introduced into the deposition chamber, and the oxygen flow rate is 2.5 ml / min;

[0065] A carbon source, a hydrogen source, an oxygen source, and octamethylcyclotetrasiloxane were introduced into the deposition chamber at a flow rate of 1.5 ml / min.

[0066] When the carbon source and the hydrogen source are introduced into the deposition chamber, the air inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle of 20°; the rotation speed of the rotating table is 0.25 r / min; and the deposition speed on the surface of the deposition material is 4.5 μm / h.

[0067] The rough surface of the biocompatible diamond composite material is polished and ground to obtain the biocompatible diamond composite material;

[0068] When the rough surface of the biocompatible diamond composite material is polished and ground, 13 μm to 28 μm diamond micropowder is used for grinding, and 0.25 μm to 8 μm diamond micropowder is used for polishing;

[0069] After the rough surface of the biocompatible diamond composite material is polished and ground, it is disinfected. First, use medical alcohol for preliminary cleaning, then use a neutral multi-enzyme cleaner, and then use an ultrasonic cleaner to clean it. Boil it for disinfection. Do not use lubricants to lubricate it to avoid residues. After drying in a drying cabinet, package it, and then use a high-temperature and high-pressure sterilizer or an epoxy-acetylene sterilizer for sterilization to meet the conditions for use.

[0070] Embodiment 2:

[0071] The same contents as those in Example 1 are not described in detail here. The differences between this embodiment and Example 1 are as follows:

[0072] This embodiment provides a method for preparing a biocompatible diamond composite material at low temperature, which also includes:

[0073] The flow rates of the carbon source and hydrogen source are adjusted in sections;

[0074] The flow rate of the first section carbon source is 21 ml / min, the flow rate of the hydrogen source is 510 ml / min, and the flow rate of octamethylcyclotetrasiloxane is 1.5 ml / min;

[0075] In the second stage, the carbon source flow rate is 24 ml / min, the hydrogen source flow rate is 500 ml / min, and the oxygen flow rate is 2.5 ml / min;

[0076] The carbon source flow rate in the third stage is 28 ml / min, and the hydrogen source flow rate is 470 ml / min;

[0077] The carbon source flow rate in the fourth stage is 0, and the hydrogen source flow rate is 470 ml / min.

[0078] The deposition temperature in the first deposition chamber is controlled at 680°C; the deposition temperature in the second deposition chamber is controlled at 400°C; the deposition temperature in the third deposition chamber is controlled at 510°C; and the deposition temperature in the fourth deposition chamber is controlled at 660°C.

[0079] The deposition material includes silicon nitride; the deposition material pretreatment includes the following steps: surface treatment of the deposition material, preparation of a surface treatment liquid, wherein the surface treatment liquid includes an alkali solution with a mass fraction of 1.5%;

[0080] Soaking the deposited material in the surface treatment solution for 2.6 minutes;

[0081] The deposited material was then ultrasonically shaken in water for 18 min, washed with ethanol, and dried for later use.

[0082] The substrate material is silicon;

[0083] When the carbon source and the hydrogen source are introduced into the deposition chamber, the air inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle of 28°; the rotating table rotates at a speed of 0.28 r / min; and the deposition speed on the surface of the deposition material is 4-5 μm / h.

[0084] Embodiment 3:

[0085] The same contents as those in Example 1 are not described in detail here. The differences between this embodiment and Example 1 are as follows:

[0086] This embodiment provides a method for preparing a biocompatible diamond composite material at low temperature, which also includes:

[0087] The flow rates of the carbon source and hydrogen source are adjusted in sections;

[0088] The flow rate of the first section carbon source is 21.5 ml / min, the flow rate of the hydrogen source is 515 ml / min, and the flow rate of octamethylcyclotetrasiloxane is 1.8 ml / min;

[0089] The second section has a carbon source flow rate of 25 ml / min, a hydrogen source flow rate of 510 ml / min, and an oxygen flow rate of 2.7 ml / min;

[0090] The carbon source flow rate in the third section is 29 ml / min, and the hydrogen source flow rate is 476 ml / min;

[0091] The carbon source flow rate in the fourth section is 0, and the hydrogen source flow rate is 470 ml / min.

[0092] The deposition temperature in the first deposition chamber is controlled at 690°C; the deposition temperature in the second deposition chamber is controlled at 430°C; the deposition temperature in the third deposition chamber is controlled at 530°C; and the deposition temperature in the fourth deposition chamber is controlled at 690°C.

[0093] The deposition material includes one of zirconium oxide and silicon nitride. The deposition material pretreatment includes the following steps: surface treating the deposition material, preparing a surface treatment liquid, wherein the surface treatment liquid includes an alkali solution with a mass fraction of 1.2%;

[0094] Soaking the deposited material in the surface treatment solution for 5 minutes;

[0095] The deposited material was then ultrasonically vibrated in water for 12 min, washed with ethanol, and dried for later use.

[0096] The substrate is made of silicon. When a carbon source and a hydrogen source are introduced into the deposition chamber, the air inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle of 16°. The rotating table rotates at a speed of 0.23 r / min. The deposition speed on the surface of the deposition material is 4-5 μm / h.

[0097] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the present application.

Claims

1. A method for preparing a biocompatible diamond composite material at low temperature, characterized in that: The following steps are involved: Selecting a deposition material with biological activity and pre-treating the deposition material; Placing the pre-treated deposition material on the upper part of the substrate in the deposition chamber, with the deposition surface of the deposition material facing upward; a rotating table is provided in the deposition chamber, and the substrate is arranged on the rotating table; Turning on the microwave generator in the deposition chamber; A carbon source and a hydrogen source are introduced into the deposition chamber, and the deposition temperature in the deposition chamber is controlled at 350-750° C. by a microwave generator; the rotating table is turned on; Depositing a diamond film layer on the upper surface of the deposition material to obtain a crude biocompatible diamond composite material; The rough surface of the biocompatible diamond composite material is polished and ground to obtain the biocompatible diamond composite material.

2. The method for preparing a biocompatible diamond composite material at low temperature according to claim 1, characterized in that: The deposition material includes one of zirconium oxide and silicon nitride.

3. The method for preparing a biocompatible diamond composite material at low temperature according to claim 1, characterized in that: The pretreatment of the deposition material comprises the following steps: surface treating the deposition material, preparing a surface treatment liquid, wherein the surface treatment liquid comprises H2SO4 and H2O2 in a volume ratio of 1:10, or the surface treatment liquid comprises an alkali solution with a mass fraction of 1%-2%; Soaking the deposited material in the surface treatment solution for ≥2 minutes; The deposited material is then ultrasonically shaken in water for 10-20 minutes, and then cleaned with ethanol and wiped dry for later use.

4. The method for preparing a biocompatible diamond composite material at low temperature according to claim 1, characterized in that: The matrix material is one of silicon, molybdenum and graphite.

5. The method for preparing biocompatible diamond composite material at low temperature according to claim 1, characterized in that: The hydrogen source introduced into the deposition chamber is hydrogen; the carbon source introduced is methane; The hydrogen source flow rate is 450-520 ml / min, and the carbon source flow rate is 20-30 ml / min.

6. The method for preparing biocompatible diamond composite material at low temperature according to claim 5, characterized in that: A carbon source and a hydrogen source are introduced into the deposition chamber, and at the same time, oxygen is introduced into the deposition chamber, and the oxygen flow rate is 2-3 ml / min.

7. The method for preparing biocompatible diamond composite material at low temperature according to claim 6, characterized in that: A carbon source, a hydrogen source, an oxygen source, and octamethylcyclotetrasiloxane are introduced into the deposition chamber at the same time, and the flow rate of the octamethylcyclotetrasiloxane is 1-2 ml / min.

8. The method for preparing biocompatible diamond composite material at low temperature according to claim 1, characterized in that: When the carbon source and the hydrogen source are introduced into the deposition chamber, the gas inlets of the carbon source and the hydrogen source rotate around the rotating table at a certain angle, and the rotation angle is 10-30°; The rotation speed of the rotating table is 0.2-0.3r / min; The deposition rate on the deposition material surface is 4-5μm / h.

9. The method for preparing biocompatible diamond composite material at low temperature according to claim 7, characterized in that: The flow rates of the carbon source and hydrogen source are adjusted in sections; The flow rate of the first section carbon source is 20-22 ml / min, the flow rate of the hydrogen source is 490-520 ml / min, and the flow rate of octamethylcyclotetrasiloxane is 1-2 ml / min; The second section has a carbon source flow rate of 23-26 ml / min, a hydrogen source flow rate of 490-520 ml / min, and an oxygen flow rate of 2-3 ml / min; The carbon source flow rate in the third stage is 27-30 ml / min, and the hydrogen source flow rate is 460-480 ml / min; The carbon source flow rate in the fourth stage is 0, and the hydrogen source flow rate is 460-480 ml / min.

10. The method for preparing biocompatible diamond composite material at low temperature according to claim 9, characterized in that: The deposition temperature in the first deposition chamber is controlled at 600-750°C; the deposition temperature in the second deposition chamber is controlled at 350-450°C; the deposition temperature in the third deposition chamber is controlled at 460-560°C; the deposition temperature in the fourth deposition chamber is controlled at 570-750°C.